1995
DOI: 10.1063/1.359946
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between deep level defects in GaAs induced by gamma, 1 MeV electron, and neutron irradiation

Abstract: The deep level transient spectroscopy technique has been employed to follow closely the effect of 1–300 Mrad 60Co γ irradiation on the deep electron traps in undoped vapor-phase-epitaxy n-type GaAs. The 1 Mrad γ-irradiated Schottky device was identical to the as-grown or control device, with only two electron traps EL2 (Ec−0.820 eV) and EL3 (Ec−0.408 eV) detected. At a γ dose of 5 Mrad, two additional electron traps EL6 (Ec−0.336 eV) and E2 (Ec−0.128 eV) were observed. As the γ doses were increased to ≥10 Mrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…22 Multistable defect configurations and internal conversion between them have been reported for interstitial-carbon substitutional-group-V-atom pair defects in electron irradiated silicon. 23 Traps with two charge states which present strong coupling to the lattice have been observed in a variety of semiconductors, for example, in Si, 24 InP, 10 Hg y Cd 1Ϫy Te, 25 GaAs, 26 and Al x Ga 1Ϫx As, 27 which were mainly analyzed through DLTS studies without attempting such model formalism. As the DLTS technique is based on the temperature scanning method, inherent limitations of the spectral line shape due to a temperaturedependent prefactor in the capacitance transient, and the possible presence of a thermally activated capture process, may lead to a misinterpretation of the result.…”
Section: Discussion On Model Distinctionmentioning
confidence: 99%
“…22 Multistable defect configurations and internal conversion between them have been reported for interstitial-carbon substitutional-group-V-atom pair defects in electron irradiated silicon. 23 Traps with two charge states which present strong coupling to the lattice have been observed in a variety of semiconductors, for example, in Si, 24 InP, 10 Hg y Cd 1Ϫy Te, 25 GaAs, 26 and Al x Ga 1Ϫx As, 27 which were mainly analyzed through DLTS studies without attempting such model formalism. As the DLTS technique is based on the temperature scanning method, inherent limitations of the spectral line shape due to a temperaturedependent prefactor in the capacitance transient, and the possible presence of a thermally activated capture process, may lead to a misinterpretation of the result.…”
Section: Discussion On Model Distinctionmentioning
confidence: 99%
“…The irradiation of GaAs with high-energy radiation particles can produce lattice defects in the form of vacancies, defect clusters, and dislocations. Lai et al [20] reported that gamma-ray irradiation resulted in the creation of complex defects in the Ga-As system. The main effect of these lattice defects on GaAs-based devices is the creation of recombination centers, which are known to reduce the minority-carrier lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…with minimum ecological disruption and resistant to radiation. In case of semiconductors, the radiation leads to production of lattice defects in the form of vacancies, defect clusters and dislocations that influence the energy levels and alter the material parameters [6][7][8]. These defects play significant role in the performance of the devices such as sensors, solar cells, metal-oxidesemiconductor junctions, schottky diodes etc.…”
Section: Introductionmentioning
confidence: 98%